Estimation of labour supply functions using panel data: a survey - François Laisney; Winfried Pohlmeier; Matthias Staat (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1991)
This survey aims at providing the reader with a thread through the literature on the topic of panel econometrics of labour supply, reporting also on the evaluation of the data used in these studies, and summarizing their substantive results. It documents the present trend away from models that take advantage of panel data almost exclusively in order to control for unobserved heterogeneity, towards fully dynamic models where wages become endogenous and consequently the concept of wage elasticity loses much of its appeal.
Keywords: 330